The pronoun in Venda and Northern Sotho : a comparative morphological, syntactic and semantic study - Makhado, John Tshifularo (My University, 1976)
Refer to the document
Thesis (M.A. (African Languages)) -- University of the North, 1976
Keywords: Venda language; Northern Sotho language; Pronouns; Venda language; Venda language -- Pronoun; Northern Sotho language -- Pronoun